GEOMARKETING FORMING INFRASTRUCTURE OF DEALER ENTERPRISES OF REPAIR-TECHNICAL BASE OF AIC REGION - Anton Zakharin; Yury Zhevora; Roman Pavlyuk; Ekaterina Glebova; Ksenia Volkova (Вестник Северо-Кавказского федерального университета)
Organization ofrepair and servicing base of technical service envisages forming ofrational composition of enterprises of different types; determination technically of necessary and economically expedient production capacity; ground of zones of technical service; perfection of the system of mutually beneficial relations between enterprises at the market of technical services in an agrarian sphere. The dealer enterprise (DE) is considered as a system consisting of three main blocks (subsystems): services, sales and supply. The DE is unified, located on the service territory (region, edge, district), and not concentrated in one place.